Simulation And Auditing Of Network Security Based On Probabilistic Neural Network Approach - Patel, Manoj; Shrivastava, Dr. Maneesh; Deshmukh, Kavita (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
: Probabilistic Neural Network approach used for mobile adhoc network is more efficient way to estimate the network security. In this paper, we are using an Adhoc On Demand Distance Vector (AODV) protocol based mobile adhoc network. In our Proposed Method we are considering the multiple characteristics of nodes. In this we use all the parameter that is necessary in AODV. For simulation purpose we use the probabilistic neural network approach that gives more efficient and accurate results as comparison to the clustering algorithm in the previous systems was used. The performance of PNN (probabilistic neural network) approach is improvedÂ for identifying the particular attack like as wormholes, black holesÂ and selfish